2014
DOI: 10.1186/1471-2431-14-177
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of brain injury in infants with hypoxic ischemic encephalopathy at high risk for severe impairments: accuracy of MRI performed in the first days of life

Abstract: BackgroundDespite therapeutic hypothermia 30-70% of newborns with moderate or severe hypoxic ischemic encephalopathy will die or survive with significant long-term impairments. Magnetic resonance imaging (MRI) in the first days of life is being used for early identification of these infants and end of life decisions are relying more and more on it. The purpose of this study was to evaluate how MRI performed around day 4 of life correlates with the ones obtained in the second week of life in infants with hypoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 27 publications
1
27
0
5
Order By: Relevance
“…In this study, we confirmed that early MRI had a predictive value at least as good as late MRI, as was expected given the excellent agreement between early and late MRIs [8][9][10][11]. Our results were inconsistent with the results of a meta-analysis which suggested that the discriminatory power of late MRI (days 8-30) was higher than that In our study, the ADC measurements added little to the visual analysis as a prognostic tool.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In this study, we confirmed that early MRI had a predictive value at least as good as late MRI, as was expected given the excellent agreement between early and late MRIs [8][9][10][11]. Our results were inconsistent with the results of a meta-analysis which suggested that the discriminatory power of late MRI (days 8-30) was higher than that In our study, the ADC measurements added little to the visual analysis as a prognostic tool.…”
Section: Discussionsupporting
confidence: 68%
“…Recent studies demonstrated that early MRI (performed in the first week of life) could reliably predict the extent and severity of brain injury observed on later MRI (performed after day 7, considering the first day of life as day 1) in asphyxiated neonates treated with hypothermia [7][8][9][10][11]. Nevertheless, to our knowledge, the prognostic value of early and late MRI had not been compared in these neonates.…”
Section: Introductionmentioning
confidence: 98%
“…Diffusion-weighted MRI has been shown to be generally sensitive to early ischemic brain changes 4 . Generation of apparent diffusion coefficient (ADC) maps and calculating ADC values allow obtaining an objective measure of diffusion abnormality 5 .…”
Section: Introductionmentioning
confidence: 99%
“…МР-исследование детям периода новорожденности обязательно выполняется с реанимационным сопро-вождением, применяется седация, предпочтительно проведение исследования во время физиологиче-ского сна [30]. С целью своевременного проведения терапии ГИЭ у доношенных новорожденных реко-мендуется выполнять МРТ головного мозга в пер-вые 3-5 суток жизни [2].…”
unclassified